ChemInform Abstract: Polyoxometalate Multi‐Electron‐Transfer Catalytic Systems for Water Splitting. Issue 13 (1st April 2014) - Sumliner, Jordan M.; Lv, Hongjin; Fielden, John; Geletii, Yurii V.; Hill, Craig L.
Abstract Review: <100 refs.